Crevice corrosion of austenitic and duplex stainless steels in seawater - Masters, G. L. (Cranfield University, 1994)
Duplex stainless steels are finding increasing use in seawater applications, but are prone to attack by crevice corrosion. A mechanism of deaeration and acidification is thought to produce locally aggressive conditions within the crevice. A variety of experimental techniques were therefore used to investigate the crevice corrosion resistance of some commercial duplex stainless steels in seawater and other, more aggressive Cr-containing environments. The established marine grade 316L austenitic stainless steel was used for reference purposes. The investigations provided both quantitative data regarding alloy performance, and qualitative observations regarding the attack mechanism. The crevice corrosion resistance of the duplex stainless steels was shown to be superior to that of 316L, and to increase with (Cr + N) content. Electrochemical polarisation scans demonstrated the importance of dissolved 02 in the seawater in maintaining a protective passive film on these alloys. Active peak current density, a measure of the severity of attack, was shown to increase with decreasing pH. In a simulated crevice solution, the duplex alloys were shown to exhibit both a narrower active range and lower peak current density than 316L. Potentiostatic tests showed weight loss to be an order of magnitude lower for the duplex alloys. Measured weight losses were in agreement with those predicted from polarisation data. The technique suggested that cathodic protection potentials as noble as -600 mV (SCE) may be sufficient to protect duplex stainless steels in seawater. Metallographic observation and electron beam analysis showed that the attack mode is potential dependent, with ferrite and austenite preferentially attacked at more active and noble potentials respectively. Real time tests showed that the internal crevice pH of austenitic stainless steel could fall to as low as 1.3. The rise in corrosion current was found to be a reliable indicator of attack, and was consistent with measured weight loss. Potential shifts were found to be relatively insensitive indicators of breakdown.